Time‐resolved femtosecond CARS from 10 to 50 Bar: collisional sensitivity1. (26th March 2013) - Wrzesinski, Paul J.; Stauffer, Hans U.; Kulatilaka, Waruna D.; Gord, James R.; Roy, Sukesh
Abstract : Femtosecond time‐resolved coherent anti‐Stokes Raman scattering (CARS) measurements are performed on neat N2 and O2 as well as on N2 in the presence of various collisional partners to examine the effects of collisions on the observed signal at pressures as high as 50 bar. An exponential‐gap energy‐corrected‐sudden (ECS‐E) scaling law is used to model the rotational energy transfer of pure N2 at these elevated pressures. After accounting for line‐mixing effects, the long‐time collisional decay (20–60 picoseconds behavior observed here is consistent with the behavior observed in previous time‐resolved CARS studies over the pressure range 0–5 bar. Despite the observation of significant pressure dependence on long‐delay timescales, the experimental results demonstrate negligible dependence on pressure and identity of colliding partner during the first 1–3 picoseconds, a time range that has been shown previously to be highly sensitive to temperature. These results suggest that a variety of recently developed time‐resolved CARS approaches that allow accurate thermometric measurements to be made over this short 1–3 picosecond range can be used at pressures up to 50 bar without the need to employ models accounting for collisional decay. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : Time‐resolved fs‐coherent anti‐Stokes Raman scattering (CARS) measurements on neat gases and gas mixtures at pressures up to 50 bar exhibit no dependence on the system pressure during the first 1–3 picoseconds. This is significant in that most CARS diagnostic approaches require accurate modeling of pressure‐dependent effects, which proves to be challenging over large pressure ranges using traditional scaling‐law treatment of rotational energy transfer.